2010
DOI: 10.3732/ajb.1000032
|View full text |Cite
|
Sign up to set email alerts
|

Mixed mating in a recently derived self‐compatible population of Leavenworthia alabamica (Brassicaceae)

Abstract: The results of our experiments suggest that mixed mating is not maintained by selection against self-pollen or zygotes in this population. Mixed mating is most likely a byproduct of the pollination process but may also be a transitional stage during the evolution of higher selfing rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 81 publications
6
19
1
Order By: Relevance
“…6). Interestingly, SC phenotypes have been observed in nearly every population, as would be predicted if these mutations are held at some low frequency when inbreeding depression is high (Busch et al 2010a). In this species, there appear to be two origins of selfing, which are associated with the total collapse of genetic diversity at the S-locus, as would be expected (Fig.…”
Section: The Genetic Basis Of Transitions From Si To Scmentioning
confidence: 78%
See 2 more Smart Citations
“…6). Interestingly, SC phenotypes have been observed in nearly every population, as would be predicted if these mutations are held at some low frequency when inbreeding depression is high (Busch et al 2010a). In this species, there appear to be two origins of selfing, which are associated with the total collapse of genetic diversity at the S-locus, as would be expected (Fig.…”
Section: The Genetic Basis Of Transitions From Si To Scmentioning
confidence: 78%
“…Based upon this observation, Lloyd inferred that small populations are more likely than large populations to shift to selfing. A recent study supports this view, as the fruit set of SI plants appears to decline in small glades (Busch et al 2010a), but comparisons of SI and SC phenotypes within a number of natural populations suggests fairly uniform selection for selfing because of its seed advantage, regardless of the population size (Busch 2005).…”
Section: Ecology and The Levels Of Selection Favoring Selfingmentioning
confidence: 84%
See 1 more Smart Citation
“…Lande and Schemske (1985) predicted only two stable endpoints of the evolution of a mating system: predominant outcrossing with strong inbreeding depression (δ > 0.5) and predominant selfing with weak inbreeding depression (δ < 0.5). They suggested that mixed mating (MM) in many species may represent transitional states or incidental by-products of other adaptive mechanisms Porcher et al, 2009;Busch et al, 2010). In contrast, increasing evidence suggests that MM is evolutionarily stable in seed plants (Goodwillie et al, 2005;Davis and Turner-Jones, 2008;Winn and Moriuchi, 2009;Thiele et al, 2010), even if they possess strong inbreeding depression (Goodwillie et al, 2005) or in obligately outcrossing species (Crawford et al, 2010).…”
Section: Evolutionary Controversy: Reproductivementioning
confidence: 95%
“…If opportunities for outcrossing are limited, selfing can be selected even if inbreeding depression is strong. In natural populations, inbreeding depression often varies among different populations (Weber and Goodwillie, 2009), isolated patches within a population (Kolehmainen et al, 2010), individuals (Busch et al, 2010), life-cycle stages (Gonzalez-Varo and Traveset, 2010;Hirao, 2010), generations (Glaettli and Goudet, 2006;Ferriol et al, 2011), and stressful environmental conditions (Cheptou, 2006). This variation is important for the evolution and maintenance of MM systems (Thiele et al, 2010), and the relative composition of inbred and outbred plants, which in a natural population is determined directly by population selfing rate, substantially influences the magnitude of inbreeding depression (Cheptou and Schoen, 2007).…”
Section: Inbreeding Depression Vs Self-evolutionmentioning
confidence: 98%